( x + 3 ) ( x + 4 ) ( x + 6 ) ( x + 7 ) = 1 1 2 0 + 1
Find the sum of all real x satisfying the equation above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Actually, you haven't shown the main part! You should show that only one of the two equations produce real roots. This can be done by examination of approximations of Δ values of the two equations. We will get non-negative Δ value for only one equation out of the two and hence we conclude by Vieta's formula that the sum is − 1 0 .
Note: For those who don't know, Δ here refers to the discriminant of a quadratic equation.
Log in to reply
You are right. I have edited the solution. When I solved the problem, I actually calculate out the actual values of the two x . So I have eliminated the two other roots because of negative square roots. Then I noticed there is an easier way to explain this without realising the negative determinant part.
( x + 3 ) ( x + 4 ) ( x + 6 ) ( x + 7 ) = ( x 2 + 7 x + 1 2 ) ( x 2 + 1 3 x + 4 2 ) = ( x 4 + 1 3 x 3 + 4 2 x 2 + 7 x 3 + 9 1 x 2 + 2 9 4 x + 1 2 x 2 + 1 5 6 x + 5 0 4 ) = ( x 4 + 1 3 x 3 + 7 x 3 + 4 2 x 2 + 9 1 x 2 + 1 2 x 2 + 2 9 4 x + 1 5 6 x + 5 0 4 ) = x 4 + 2 0 x 3 + 1 4 5 x 2 + 4 5 0 x + 5 0 4 .
Then, maybe hard to solve this biquadratic equation.
( x 2 + 1 0 x + 2 1 ) ∗ ( x 2 + 1 0 x + 2 4 ) = 1 1 2 1 t = x 2 + 1 0 x + 2 1 t 2 + 3 t − 1 1 2 1 = 0 ( ∗ ) The equation (*) has one root that is: t = 2 4 4 9 3 − 3 Solving the eq: x 2 + 1 0 x + 2 1 − 2 4 4 9 3 − 3 = 0 Get two roots for the equation that have sum is: S u m = 1 0
sum = − 1 0 , not 1 0
Let's do x = v − 5 ; v ² = u + 2 . 5 .. Then we have: ( x + 3 ) ( x + 4 ) ( x + 6 ) ( x + 7 ) = 1 1 2 1
( v − 2 ) ( v − 1 ) ( v + 1 ) ( v + 2 ) = 1 1 2 1
( v 2 − 1 ) ( v 2 − 4 ) = 1 1 2 1
( u + 1 . 5 ) ( u − 1 . 5 ) = 1 1 2 1
u 2 − 2 . 2 5 = 1 1 2 1
u = + − 2 . 2 5 + 1 1 2 1
As v 2 = u + 2 . 5 > 0 , u = + 2 . 2 5 + 1 1 2 1 .
v = + − 2 . 5 + 2 . 2 5 + 1 1 2 1 and
x = − 5 + − 2 . 5 + 2 . 2 5 + 1 1 2 1
The sum: x 1 + x 2 = − 5 + 2 . 5 + 2 . 2 5 + 1 1 2 1 − 5 − 2 . 5 + 2 . 2 5 + 1 1 2 1 = − 5 − 5 = − 1 0
ps: x = + − a is my notation for x=a or x=-a.
Let x + 5 = y then:
( y − 2 ) ( y − 1 ) ( y + 1 ) ( y + 2 ) = 1 1 2 1
( y 2 − 1 ) ( y 2 − 4 ) = 1 1 2 1
y 4 − 5 y 2 + 4 = 1 1 2 1
y 4 − 5 y 2 − 1 1 1 7 = 0
In here, according to Vieta's formula, no matter what the c value is in a x 2 + b x + c = 0 , the sum of two roots for x is always a − b . Hence in this case, the sum of roots for y 2 = 5 .
Substituting again for x,
( x + 5 ) 2 = 5
x 2 + 1 0 x + 2 5 = 5
x 2 + 1 0 x + 2 0 = 0
*Note that we can still substitute y 2 to ( x + 5 ) 2 despite that it is an equal sign for their sum of roots, because it is also the two roots of x that's been put in the quadratic equation to add to that number (5).
Hence, using the Vieta's formula again, the summation of the two values of x is 1 − 1 0 = − 1 0
There is only 1 x>0 which satisfies the equation. Then -x-10 is the only other solution where x<0 , then we get -(x+3) ×-(x+4)×-(x+6)×-(x+7)=(x+3)(x+4)(x+6)(x+7)=1120+1. So x+(-x-10)=-10
Problem Loading...
Note Loading...
Set Loading...
Let y = x + 5 , then:
( x + 3 ) ( x + 4 ) ( x + 6 ) ( x + 7 ) ( y − 1 ) ( y − 2 ) ( y + 1 ) ( y + 2 ) ( y 2 − 1 ) ( y 2 − 4 ) y 4 − 5 y 2 + 4 y 4 − 5 y 2 − 1 1 1 7 y 2 ⇒ ( x + 5 ) 2 ⇒ x 2 + 1 0 x + 2 5 − 2 5 + 4 4 9 3 = 1 1 2 1 = 1 1 2 1 = 1 1 2 1 = 1 1 2 1 = 0 = 2 5 ± 4 4 9 3 = 2 5 ± 4 4 9 3 = 0
Using Vieta's formula, the sum of x satisfying the equation = − 1 0